1999
DOI: 10.1016/s0005-2736(99)00129-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hexavalent chromium on eukaryotic plasma membrane studied by EPR spectroscopy

Abstract: The effect of Cr(VI) anion on an ergosterol-producing strain of eukaryotic yeast Candida albicans and its mutant with ergosterol-less membrane was studied with EPR spectroscopy. 5- and 14-doxyl stearic acid spin probes were used to label the protoplast membrane after removal of the cell wall. In control experiments, the mutant strain exhibited larger rigidity in the membrane than its parental strain. Addition of Cr(VI), at a minimum inhibitory concentration of 0.6 mM, increased the rotational mobility of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…The facilitated diffusion of CrO 4 2-into the cells started immediately after CrO 4 2-addition (BELÁGYI et al 1999). After pretreatment of S. pombe cultures with 250 µM K 2 Cr 2 O 7 for 120 min (BELÁGYI et al 1999), the chr1-66T mutant accumulated half as much Cr(VI) as did its parental strain (data not presented).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The facilitated diffusion of CrO 4 2-into the cells started immediately after CrO 4 2-addition (BELÁGYI et al 1999). After pretreatment of S. pombe cultures with 250 µM K 2 Cr 2 O 7 for 120 min (BELÁGYI et al 1999), the chr1-66T mutant accumulated half as much Cr(VI) as did its parental strain (data not presented).…”
Section: Resultsmentioning
confidence: 94%
“…After pretreatment of S. pombe cultures with 250 µM K 2 Cr 2 O 7 for 120 min (BELÁGYI et al 1999), the chr1-66T mutant accumulated half as much Cr(VI) as did its parental strain (data not presented). The time-course of Cr(V) formation and reduction monitored by EPR spectroscopy indicated that both strains reduced Cr(VI) to Cr(III) through Cr(V), but the elimination of Cr(V) in the Cr(VI)-tolerant chr1-66T mutant was much slower than in 6chr + cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several findings suggest that trace elements, e.g., iron, copper, zinc, selenium, chromium, cadmium, mercury and lead may influence membrane fluidity. In particular, hexavalent chromium (Cr 6+ ), which is well recognized to pose an environmental health risk, has been shown to increase membrane fluidity [50]. Consistent with this membrane change having an insulin-like action on glucose transport, hexavalent chromium significantly stimulates glucose uptake into rat adipocytes [39].…”
Section: Discussionmentioning
confidence: 94%
“…It was demonstrated that ergosterol-less mutants with a modified plasma membrane structure exhibit Cr(VI) changed sensitivity [21]. The modified tolerance of the mu-tant cells to chromate is accompanied with the changes in Cr(VI) uptake and chromium bioaccumulation [22].…”
Section: Introductionmentioning
confidence: 99%